The role of placenta Hofbauer cells during pregnancy and pregnancy complications - Seung-Woo Yang; Han-Sung Hwang; Young-Sun Kang (Obstetrics & Gynecology Science)
Placental Hofbauer cells (HBCs) are specialized macrophages present in the human placenta that play a crucial role in maintaining a healthy pregnancy. These cells are derived from the fetal mesoderm and are responsible for various functions, including immune regulation, angiogenesis, and nutrient transport. In normal pregnancies, HBCs primarily exhibit an M2 or immunomodulatory phenotype, which helps maintain a tolerant and antiinflammatory environment at the maternal-fetal interface. However, in pregnancies complicated by conditions such as immunological disorders, inflammation, or infection, the phenotype and function of HBCs may be altered. Although emerging evidence has highlighted the vital role of HBCs in both normal pregnancies and those with complications, such as chorioamnionitis, gestational diabetes, preeclampsia, and viral infections, their role remains unclear. Recent research also suggests a relationship between HBCs and the development of diseases in offspring. Understanding the role of HBCs in pregnancy could provide insights into the pathophysiology of various pregnancy-related disorders and offer potential therapeutic targets for improving maternal and fetal outcomes. This review explores the functions of HBCs in normal pregnancy and their involvement in complications, emphasizing their potential as biomarkers or targets for interventions aimed at reducing the incidence of adverse pregnancy outcomes. Additionally, we reviewed their potential for perinatal research in recent studies.